Determination of the Air Hitam River, Pekanbaru CityWater Quality Based Biotic Index Macrozoobenthos - Fery Permadi; Nur El Fajri; Adriman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from January to February 2014 in the Air Hitam River,the city of Pekanbaru. This research aims to determine the condition of the Air Hitam Riverwater quality in terms of some aspects of physics, chemistry and biology macrozoobenthosorganisms. . There were 4 stations and 3 sampling points in each station. Water samples weretaken 3 times, once/ week. Water quality parameters measured were temperature, turbidity,current speed, total suspended solid, DO, pH, BOD and COD. While macrozoobenthos dataanalysis using the FBI index (Family Biotic Index).The results show that there are 9 classes / order, namely Gastropod (5 families),Trichoptera (2 families), Diptera (2 families), Ephemeroptera (1 family), Coleoptera (1family), Polydesmida, nematodes, Hydracarina and Oligochaeta. Water quality parametersare as follows: Temperature: 27.67-29.33 0C, turbidity: 9-17.56 NTU, current speed: 6-35cm/s, total suspended solid: 4.67-7.78 mg/l, DO: 4.96 -6.73 mg/l, COD: 22.40-38.40 mg/l,BOD5: 1.40-4.42 mg/l and pH: 5. Based on the Family Biotic Index macrozoobenthos, it canbe concluded that the level of water pollution in the Air Hitam River ranged from 5.31(polluted enough) to 6.93 (very much polluted). Based Storet Index, it can be concluded thatthe level of water pollution in the Air Hitam River is being polluted.Keywords : Air Hitam River, Water Quality, Family Biotic Index macrozoobenthos.